What's the secret? : to providing a world-class customer experience - DiJulius, John R., 1964- (Wiley, 2008)
"Author John DiJulius, considered the authority on customer service, has cracked the code through his extensive experience at helping large companies deliver superior service, and he knows the best practices of the world-class customer service companies. Now, he shares that inside knowledge and shows readers how to emulate these high standards of service in their own businesses, no matter how small or how large. With proven action steps and non-negotiable customer service standards, any business owner or leader can differentiate their business by becoming a customer service powerhouse."--Jacket.